Sustaining polio-free Indonesia through enhanced capacity of primary and secondary target groups: a case study in primary health care services - Kusumaratna, Rina; Aureyll, Daffa; Laksmi, Ni Putu; Hastari, Shalsa; Suci, Witriastika (Universitas Gadjah Mada, 2024)
Purpose: Indonesia strives to remain polio-free and eradicate polio globally by 2026, adding two inactivated polio vaccine (IPV) vaccine doses to the 2023 child immunization schedule. IPV2 immunization has been introduced in DKI Jakarta, West Java, and Banten provinces. This initiative aims to enhance public health by protecting against vaccine-preventable diseases. Methods: A mixed-method study was conducted in December 2022 - January 2023 at South Jakarta, Mampang Prapatan district health center, focusing on IPV2's second dose introduction evaluation. Results: Effective health promotion and seamless integration of primary health services are pivotal in implementing vaccination services. Despite ongoing understanding gaps, health cadres and parents showed significant knowledge gains (p<0.05) post-intervention. The health cadres' role in education is crucial. Conclusion: Aligned with the tiered health transformation, which has evolved into a collaborative movement grounded in the life cycle, health cadres' effective deployment and support play a pivotal role in sustaining Indonesia’s polio-free achievement.